CHANGES IN LANGUAGE: THE COMPARATIVE AND HISTORICAL METHOD IN LINGUISTICS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores how languages evolve over time through the comparative and historical method, highlighting the underlying principles and techniques used to track linguistic change. By examining examples from Indo-European languages, the paper discusses the significance of phonetic, grammatical, and lexical changes in understanding language relationships and origins. It underscores the importance of the comparative method for reconstructing linguistic histories and its contributions to modern linguistics.